2022
DOI: 10.2147/idr.s369240
|View full text |Cite
|
Sign up to set email alerts
|

Septic Arthritis Complicating Arthroscopic Anterior Cruciate Ligament Reconstruction: An Experience from a Tertiary-Care Hospital

Abstract: Background Septic arthritis (SA) of the knee following anterior cruciate ligament reconstruction (ACLR) is considered a catastrophic complication in terms of reduced or loss function of the involved joint. The aims of this study were to gauge the incidence, risk factors, and causative organisms of SA after ACLR. Methods We conducted a retrospective review of 836 patients who underwent primary ACLR at our institution from October 2018 to September 2021. Patients’ demogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Numerous studies have shown positive outcomes with graft retention in the setting of post-ACL-R infection, in which the graft appears healthy during the first I&D 18,19 . However, all patients with successfully retained grafts reported no continuing signs of infections after initial debridement and intravenous antibiotics 18,19 . In cases when the infection continues and further debridement is necessary, 1 treatment algorithm from Geethan et al identified that graft removal becomes a priority.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have shown positive outcomes with graft retention in the setting of post-ACL-R infection, in which the graft appears healthy during the first I&D 18,19 . However, all patients with successfully retained grafts reported no continuing signs of infections after initial debridement and intravenous antibiotics 18,19 . In cases when the infection continues and further debridement is necessary, 1 treatment algorithm from Geethan et al identified that graft removal becomes a priority.…”
Section: Discussionmentioning
confidence: 99%
“…On initial presentation, hardware removal was our foremost consideration. Numerous studies have shown positive outcomes with graft retention in the setting of post-ACL-R infection, in which the graft appears healthy during the first I&D 18,19 . However, all patients with successfully retained grafts reported no continuing signs of infections after initial debridement and intravenous antibiotics 18,19 .…”
Section: Discussionmentioning
confidence: 99%
“…Other studies exist that suggest DM is not a risk factor for infection after ACLR, although these may reflect a lack of power rather than robust findings. Multiple national database studies have found no increased infection risk because of DM within 30 days postoperatively 12,13 ; although one of the studies reported an infection rate of 5.1% in patients with DM undergoing ACLR compared with 1.7% in patients without DM, the P -value was 0.14 22 . Similarly, a study out of India reported an OR for developing an infection after ACLR in patients with DM of 4.8, but the P -value was 0.16 14 .…”
Section: Infectionmentioning
confidence: 99%
“…Using the MOON database to identify a cohort of 2,291 patients who underwent Bankart repair for labral injuries, DeFroda et al 20 found that DM increased risk for readmission (OR = 2.70). Manzi et al 13 identified DM as a risk factor for readmission within 30 days after ACLR (OR = 2.14) in a large database study of 9,576 patients. Finally, Christian et al 21 conducted a retrospective case-control study within 5,598 patients who underwent shoulder arthroscopy and found DM increased risk of readmission (OR = 2.11).…”
Section: Postoperative Readmissionmentioning
confidence: 99%